Evaluation of Verbal Working Memory and Phonemic Analysis Skills in Adolescents with Cochlear Implant* - Gökay, Nuriye Yildirim; Atalik, Güzide; Trank, Şadiye Bacik; Tutar, Hakan; Karamert, Recep; Gündüz, Bülent (International Archives of Otorhinolaryngology, 2023)
Introduction Adolescents with cochlear implants may have difficulty developing language and memory abilities.Objective The primary objectives of this study are (1) to evaluate the language skills and verbal working memory performance of early and late diagnosed-intervened cochlear implanted adolescents and (2) to investigate the relationship between the verbal working memory and phonemic analysis skills in adolescents with cochlear implant.Methods This study included 72 participants with cochlear implant aged between 10 and 18 years. The participants were divided into two groups; those who had first hearing aid at the age of 6 months at the latest and had a first cochlear implant in at least one ear at the latest at 24 months were included in the early group, all the others were in the late group. The phonemic analysis test, a subtest of the test of language development: Primary, 4th edition (TOLD: P-4) – Turkish version, was used to assess language-based abilities, and the meaningless word repetition (MWR) test was utilized to assess verbal working memory.Results The adolescents with cochlear implants who received early diagnosis and intervention performed statistically significantly better in phonemic analysis scores and verbal working memory tests (p < 0.001). A statistically significant relationship was found between phonemic analysis and verbal working memory skills (Pearson, r = 0.567 and r = 0.659, p < 0.001).Conclusions Rehabilitation of phonological skills can contribute to the development of verbal working memory in adolescents with cochlear implants. There is a need for further studies on this issue with more detailed tests.
Keywords: working memory; phonemic analysis; cochlear implant; adolescents